Ethnomathematics-Based Contextual Learning to Improve Students’ Mathematical Reasoning Ability - Nuraimah Suharto; Sukmawati Sukmawati; Muhammad Assaibin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Mathematical reasoning is a key component of mathematics learning because it enables students to develop logical, critical, and systematic thinking. However, students’ reasoning ability often remains underdeveloped when instruction focuses mainly on procedures and provides limited opportunities to connect mathematical concepts with real-life contexts. This study examined the improvement of students’ mathematical reasoning ability through ethnomathematics-based contextual learning. A quantitative pre-experimental design with a one-group pretest-posttest model was employed. The participants were fifth-grade students at SDN 002 Campalagian in the 2025/2026 academic year. Data were collected using an essay-based mathematical reasoning test and an observation sheet of students’ learning activities. The data were analyzed using descriptive statistics, N-Gain analysis, and a paired-sample t-test. The findings showed that students’ mathematical reasoning ability improved after the implementation of ethnomathematics-based contextual learning. The N-Gain results indicated a moderate to high level of improvement, and the paired-sample t-test showed a statistically significant difference between the pretest and posttest scores. Observation data also indicated that students were actively engaged during the learning process. These findings suggest that ethnomathematics-based contextual learning can support the development of students’ mathematical reasoning ability by linking mathematical ideas to meaningful cultural and real-life contexts. This approach can be considered an alternative instructional strategy for promoting more meaningful mathematics learning in elementary classrooms.